The Noble Suicide: The Case of a Self-Contained Dagger in the Heart and a Literal Raw - Maricla Marrone; Benedetta Pia De Luca; Marco Papalino; Fortunato Pititto; Carlo Angeletti; Roberto Bellacicco; Michela Raino; Giuseppe Pulin; Francesca Tarantino (Case Reports in Psychiatry)
According to WHO estimates, more than 700,000 people die each year due to suicide and suicides performed with a bladed weapon account for approximately 1.6%–3% of all suicides. It is statistically more common to find injuries to the heart, lungs, and thoracic vessels in homicides, whereas in suicides there is a higher frequency of vascular injuries to the extremities of the limbs. Also in suicides, the presence of “hesitation marks,” related to the attempts the victim makes before having the courage to kill himself, can often be found. In the case presented by the authors, these parameters are subverted: There was only one injury and it was the fatal one, it was located on the chest and reached the heart. But it was suicide. The circumstantial data, the psychological explanation, and the previous similar suicide attempt left no doubt about it. The man decided to commit suicide because he could no longer find meaning in his life after losing hope for a career as a pianist, having been diagnosed with a degenerative disease in his hands. The man hated himself and his existence: The future appeared extremely negative and the only escape was self-suppression. This case report makes an essential contribution to the already existing Literature as it shows a suicide that occurred in an unusual manner.